Long-term results of secondary biliary repair for cholecystectomy-related bile duct injury: results of a tertiary referral center. Issue 2 (3rd March 2020) - Navez, Julie; Gigot, Jean-François; Deprez, Pierre H.; Goffette, Pierre; Annet, Laurence; Zech, Francis; Hubert, Catherine
Abstract: Background: Management of bile duct injury (BDI) after cholecystectomy is challenging. The authors analyzed their center's 49-year experience. Methods: From 1968 to 2016, 120 consecutive patients were managed in a tertiary HBP center, 105 referred from other centers (Group A), 15 from our center (Group B). Surgical strategies and long-term outcomes were retrospectively reviewed. Results: Primary cholecystectomy approach was open in 35% and laparoscopic in 65%. In Group A, intraoperative BDI diagnosis was made in 25/105 patients, including 13 via intraoperative cholangiography (IOC) which was used in 21% of cases. Median time from BDI to referral was 148 days (range 0–10, 758), and 3 patients had BDI-related secondary cirrhosis. Ninety-four patients underwent secondary surgical repair, mostly a complex biliary procedure (97%). Postoperative overall and severe morbidity rates were 26% and 6%, respectively. One patient with biliary cirrhosis at referral died postoperatively from hepatic failure. Nine patients (9.6%) developed a secondary biliary stricture after a median of 54 months from repair (6–228 months). In Group B, IOC was performed in 14/15 in whom BDI were intraoperatively detected and immediately repaired. There were 13 minor and 2 major BDIs, all repaired by uncomplex procedures with uneventful postoperative course. One patient had a secondary biliary stricture after 5 months, successfully treated by temporary endoprosthesis. Conclusion: Late follow-up after primary or secondary repair of BDI is recommended to detect recurrent biliary stricture. Bile duct injuries may occur in a tertiary center, but are intraoperatively detected with routine IOC and immediately repaired resulting in satisfactory outcome.